2014
DOI: 10.1080/15568318.2013.784933
|View full text |Cite
|
Sign up to set email alerts
|

Smart Devices and Travel Time Use by Bus Passengers in Vancouver, Canada

Abstract: This research investigates the usage of smart devices and time at bus stops and on buses in Vancouver, Canada. Using passive observations and self-reported surveys mainly from college students, the majority of passengers were found to use their travel time actively. Most of the observed active activities are associated with the usage of smart devices. However, while the possession of smart devices is prevalent, less than one-third of passengers used them during travel. A variety of environmental and trip facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
(75 reference statements)
2
34
0
1
Order By: Relevance
“…Although research on travel-based multitasking used to focus on public transit passengers (e.g., Guo, Derian, & Zhao, 2015;Lyons, Jain, & Weir, 2016), multimodal studies are increasing (Keseru & Macharis, 2018). Naturally, modal differences in activity participation appear, likely due to differences in required levels of operation and attention (Circella, Mokhtarian, & Poff, 2012).…”
Section: How Productive and Useful Is Travel-based Multitasking Anyway?mentioning
confidence: 99%
“…Although research on travel-based multitasking used to focus on public transit passengers (e.g., Guo, Derian, & Zhao, 2015;Lyons, Jain, & Weir, 2016), multimodal studies are increasing (Keseru & Macharis, 2018). Naturally, modal differences in activity participation appear, likely due to differences in required levels of operation and attention (Circella, Mokhtarian, & Poff, 2012).…”
Section: How Productive and Useful Is Travel-based Multitasking Anyway?mentioning
confidence: 99%
“…There were few studies of travel-based multitasking until recently (Kenyon & Lyons, 2007). Studies use different data collection methods, including field observations (Guo, Derian, & Zhao, 2015;Ohmori & Harata, 2008;Russell et al, 2011;Timmermans 6 A few scholars have wondered whether some forms of passive travel are even activities (Kenyon, 2010, p. 54;Circella et al, 2012, p. 84). For instance: The major conceptual difference between riding on/in a train/bus/taxi and cleaning clothes using a home washing machine is that passenger travel requires copresence of the traveler and the means of transportation at all times.…”
Section: Travel-based Multitaskingmentioning
confidence: 99%
“…& van der Waerden, 2008;van der Waerden, Timmermans, & van Neerven, 2009), questionnaire surveys and activity diaries (Berliner, Malokin, Circella, & Mokhtarian, 2015;Diana, 2008;Ettema, Friman, Gärling, Olsson, & Fujii, 2012;Ettema & Verschuren 2007;Frei, Mahmassani, & Frei, 2015;Guo et al, 2015;Kenyon, 2008;Kenyon & Lyons, 2007;Keseru et al, 2015;Lyons, Jain, & Holley, 2007;Lyons et al, 2013;Lyons, Jain, & Weir, 2016;Malokin et al, 2015;Mokhtarian, Papon, Goulard, & Diana, 2015;Ohmori & Harata, 2008;Yosritzal, 2014;Zhang & Timmermans, 2010), and interviews or focus groups (Handy et al, 2005;Jain & Lyons, 2008). While observations can reduce response bias and more accurately capture activity durations, self-reported survey data may be more useful for studying PUT because activities may be more closely related to underlying motivations (recall the activities vs. items discussion).…”
Section: Travel-based Multitaskingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a similar theme, Barbeau et al (2010) explored how new mobile apps enhance rider experience by providing real-time information about their trips, including alerting customers when to disembark or enabling riders to signal the driver to stop. Guo et al (2015) observed 1,739 passengers and surveyed 686 to evaluate usage patterns on the bus system in Vancouver, British Columbia. Their study used a predictive model to evaluate the factors (such as crowding and waiting conditions) that affect how riders spend their time.…”
Section: Relevant Literaturementioning
confidence: 99%